Discriminatory Discourses against Black People in 12 Years A Slave Movie: A Critical Discourse Study - Athifa Reihan Islamy; Andi Muhammad Irawan (Universitas Negeri Padang, 2023)
This research examined on the issue of racial discrimination by white people against black people. This problem can also be identified by using CDA's Van Dijks ideological square which focused on positive self-representation and negative-other representation. The researcher used descriptive qualitative research methods to analyze the data. Specifically, the researcher analyzed the discourses presented in this movie. This study focused on how white People portray themselves and other in their discourses based on their beliefs. From this movie being analyzed, the researcher has collected 44 datum that consist of the Positive-Self and Negative-Others presentation. By employing Van Dijk’s Ideological Square, the researcher found out there are 7 discourse topics implied in movie’ utterances. Furthermore, there are 9 discourse strategies used by white people in defending themselves.